Adsorption of arsenic (III) from aqueous solution by a novel phosphorus-modified biochar obtained from Taraxacum mongolicum Hand-Mazz: Adsorption behavior and mechanistic analysis. (15th August 2021) - Ahmed, Waqas; Mehmood, Sajid; Núñez-Delgado, Avelino; Ali, Sehrish; Qaswar, Muhammad; Shakoor, Awais; Maitlo, Ali Akbar; Chen, Di-Yun
Abstract: A novel phosphorus (P) modified biochar (PLBC) was produced by pyrolyzing biomass of the dietic herb Taraxacum mongolicum Hand-Mazz (TMHM) and treating it with monopotassium phosphate (KH2 PO4 ). This phosphorous loaded biochar was then assessed as adsorbent for As(III) removal from contaminated water. In the current research, the adsorbent was characterized before and after P loading by means of SEM-EDX, TEM, FTIR and XRD techniques. It was evidenced that the presence of P on the surface of the biochar (BC) could improve its efficiency to remove As(III) from contaminated environments. Adsorption kinetics were evaluated by performing batch-type experiments at varied times and pH values (5, 7 and 9). The kinetic study revealed that a contact time of 24 h was required to attain equilibrium and the experimental data were best fitted to the pseudo-second-order kinetic model (qe  = 17.1 mg g −1 ). In addition, several batch experiments were conducted with varied arsenic concentrations. During the adsorption tests, the maximum adsorption of As(III) was found at pH 5. The adsorption study further showed that compared to BC, PLBC depicted increased removal of As(III) from contaminated solutions. The adsorption experimental data showed the best fit to the Langmuir isotherm model (with R 2  = 0.84), with maximum As(III) adsorption capacity reaching 30.76 mg g −1 for PLBC. Graphical abstract: Image 1 Highlights: A novel biochar from a natural herb ( Taraxacum mongolicum Hand-Mazz) was made and modified by loading of phosphorus. PH, dosage, and contact time of modified biochar can effectively reduce As(III) contamination. The adsorption experimental data showed the best fit to the Langmuir isotherm model (with R 2  = 0.86). The modified biochar effectively alters the chemical form and mobility of As(III) in the aqueous solution. Surface complexation, co-precipitation and ion-exchange were the main immobilization mechanisms.